Крупный представитель кошачьих из плиоцена юга Украины - Короткевич, Е.Л. (Вестник зоологии, 1969)
The article deals with fragment of the left elbow bone which belongs to the large representative of Felidae from the Paleocene deposits of the valley of the Kuchurgan river of Odessa district. The bone relics of the arleady known large Felidae from the locations of hipparion fauna in the south of the European part of the USSR considerably differ from the bone under description. The fossil Felidae from other locations had more slim and slender fore-limbs. The Kuchurgan Machairodus as to its dimensions must approximate to the Pavlodar Mechairodus irtyschensis described by Yu. A. Orlov, and Epimachairodus from the Odessa Paleocene described by A. K. Alexeev.